Galactose and its Metabolites Deteriorate Metaphase II Mouse Oocyte Quality and Subsequent Embryo Development by Disrupting the Spindle Structure - Mili Thakur; Faten Shaeib; Sana N. Khan; Hamid-Reza Kohan-Ghadr; Roohi Jeelani; Sarah R. Aldhaheri; Bernard Gonik; Husam M. Abu-Soud (Scientific Reports, 2017)
Abstract Premature ovarian insufficiency (POI) is a frequent long-term complication of classic galactosemia. The majority of women with this disorder develop POI, however rare spontaneous pregnancies have been reported. Here, we evaluate the effect of D-galactose and its metabolites, galactitol and galactose 1-phosphate, on oocyte quality as well as embryo development to elucidate the mechanism through which these compounds mediate oocyte deterioration. Metaphase II mouse oocytes (n = 240), with and without cumulus cells (CCs), were exposed for 4 hours to D-galactose (2 μM), galactitol (11 μM) and galactose 1-phosphate (0.1 mM), (corresponding to plasma concentrations in patients on galactose-restricted diet) and compared to controls. The treated oocytes showed decreased quality as a function of significant enhancement in production of reactive oxygen species (ROS) when compared to controls. The presence of CCs offered no protection, as elevated ROS was accompanied by increased apoptosis of CCs. Our results suggested that D-galactose and its metabolites disturbed the spindle structure and chromosomal alignment, which was associated with significant decline in oocyte cleavage and blastocyst development after in-vitro fertilization. The results provide insight into prevention and treatment strategies that may be used to extend the window of fertility in these patients.